Computational Analysis of a High-Lift and Low Reynolds Number Airfoil at Turbulent Atmospheric Conditions - Islam, Mazharul; Amin, M. Ruhul; Shariff, Yasir M. (American Society of Mechanical Engineers (ASME), 2009)
Selection of airfoil is crucial for better aerodynamic performance and design of aerodynamic applications such as wind turbine and aircrafts. In this paper, a high-lift and lowReynolds number airfoil has been selected and investigated through computational analysis for applying it for small-sized wind turbines as blades. The S1223 airfoil, designed by the University of Illinois at Urbana-Champaign, was chosen for its high-lift characteristics at low Reynolds number typically encountered by the small wind turbines. CFD work is performed with S1223 airfoil profile over a wide range of conditions of interest to analyze the performance of the airfoil using the Spalart-Allmaras turbulence model. The results obtained from the simulation works have been compared with experimental data for validation purpose. It has been found that the Spalart-Allmaras model conforms well with the experimental results, though the values of lift coefficients (Cl) are slightly less than the experimental results. In the present analysis, velocity distributions are analyzed at different angle of attacks for different turbulence intensities. It has been observed that there is vortex shedding around the trailing edge of the airfoil for both turbulence levels. It has been observed in the present study that due to increase in turbulence intensity, both the maximum lift coefficient and the stall angle increases significantly. It has been found after investigating the effect of turbulence intensity over lift-to-drag coefficient ratio that it drastically decreases due to increase in turbulence intensity up to certain value (about 3.5%), then it starts decreasing in gradual manner. NOMENCLATURE ABL Atmospheric Boundary Layer c Blade chord CFD Computational Fluid Dynamics Cl Lift coefficient Cd Drag coefficient CTA Constant Temperature Anemometry DES Detached Eddy Simulation HAWT Horizontal Axis Wind Turbine LES Large Eddy Simulation Re Reynolds number RNG Renormalization group RSM Reynolds Stress Model 2 Copyright © 2009 by ASME T Temperature VAWT Vertical Axis Wind Turbine V∞ Wind speed Xsep Separation point on airfoil surface ρ Density α Angle of attack μ Viscosity ν Kinematic viscosity